Concurrent drought and heatwave events over the Asian monsoon region: insights from a statistically downscaling CMIP6 dataset - Lianlian Xu; Wei Yu; Song Yang; Tuantuan Zhang (Environmental Research Letters, 2024)
Concurrent drought and heatwave (CONDH) can cause tremendous ramifications on socioeconomic activities and human health, and the drought-heatwave (D-H) dependence was revealed to be one of the major factors of the CONDH across most global land regions. However, insufficient attention has been paid on the CONDH over the Asian monsoon region, and the impact of the D-H dependence is even more rarely considered. Based on a statistically downscaling the Coupled Model Intercomparison Project Phase 6 (CMIP6) dataset, we explore the spatial distributions of the intensity, frequency, and duration of the CONDH. In addition, the qualitative impacts of D-H dependence on the intensity, frequency, and duration of the CONDH have been further investigated via comparing these three metrics of the CONDH with those of heatwave. In the period of 1961–2014, the spatial pattern of intensity and duration of the CONDH bear a large resemblance to that of heatwave, with more severe CONDH (heatwave) occurring over South Asia, and relatively long-lasting CONDH (heatwave) occupying over the low latitudes of the Asian monsoon region. The frequency of the CONDH presents large discrepancies with that of heatwave. East Asia (South Asia) is hit by more frequent CONDH (heatwave) than other sub-regions. The D-H dependence is conducive to the intensity, frequency, and duration of the CONDH, especially over the East Asia, Eastern Siberia, and Western Siberia. In the period of 2015–2100, the intensity and duration of the CONDH and heatwave maintain the historical spatial structures. The frequency of the CONDH and heatwave change remarkably relative to 1961–2014, with largest value over eastern central Asia. The D-H dependence is conducive to the three features of the CONDH, and such positive contributions would weaken in response to global warming, especially under higher emission scenario.